Rethinking inclusion in higher education: Lessons for the South African academic space - Batisai, K.; Makhafola, K. P.; Maoba, P. (South African Journal of Higher Education, 2022)
Academic exclusion within higher education institutions has been an alarming global issue that has resulted in a vast number of policies aimed at combating the exclusion. In South Africa, exclusion is deeply rooted in the historical inequalities that continue to render access to higher education a complex process as visibly evidenced by structural and personal constraints even after 27 years of democracy. Content analysis in this article illuminates various factors that contribute to the exclusion or loneliness students feel in higher education. This manifests as poor performance, high dropout, and low throughput rates attributable to unsuccessful negotiation, integration, and adaptation to face-to-face and virtual academic spaces. Over the years, South African universities introduced academic mentoring programmes aimed at eliminating epistemic exclusion through a more responsive, integrative, and inclusive higher education system. Nonetheless, students’ emotional and mental wellbeing, and their ability to integrate and establish interactional relationships have been compromised by the COVID-19 pandemic. As the article rethinks inclusion in higher education, it interrogates the meaning of academic mentoring programmes for historically excluded students in a context where teaching and learning are spontaneously shifting to virtual spaces due to the pandemic.